Perencanaan Produksi Kopi Robusta (Coffea canephora) Menggunakan Metode Logika Fuzzy: Studi Kasus di PT. Perkebunan Nusantara XII Kebun Silosanen - Yuli Wibowo; Rima Malica Mukammila (JOFE : Journal of Food Engineering, 2022)
PT. Perkebunan Nusantara XII Kebun silosanen is one of the state-owned companies in Jember Regency which is engaged in the processing of robusta coffee (green bean). The problem is the mismatch between the company's plan and the seasonally variable market demand, which affects the inventory that must be held, which results in situations like stockouts and overstocks and drives up storage costs. The purpose of this study is to evaluate using two methods, namely fuzzy Tsukamoto and Mamdani. Then determine the best method using mape values and make a company production plan using 3 input variables, namely the amount of demand, inventory and quality realization. The results showed that Tsukamoto's fuzzy method was chosen as an alternative method to be used in the production plan for the next period. The MAPE value obtained is "good" because it is between 10-20%, which is 11.9%. The simulation results of Tsukamoto's fuzzy model for the production plan were carried out using the DES Brown forecasting method (supply, demand) and the SES method (quality realization). The data from the production plan using Tsukamoto fuzzy for July 2021 – December 2021 are 55,945 kg, 35,614 kg, 52,501 kg, 57,097 kg, 60,477 kg, and 61,545 kg, respectively